ASSESSING STUDENTS' TRANSLATION QUALITY ON LANG LEAV'S POEM "SHE" - Antari, Addinda Maulidita (2017)
The present research was aimed to evaluate the students' translation quality on one of Lang Leav's poems entitled "She". The qualitative method was used and case study was chosen as the research design of the study. The data were collected from two classes of Translating English-Indonesia course at an English Education Department of one state university in Indonesia. From 40 student-translators, 41 translations were obtained from the data collection. The data were then profiled and analysed based on Translation Quality Assessment model proposed by House (1997). The result of the research showed the quality of the translations produced by the student-translators, in which was measured by the mismatched occurred in the translations.